Answer:
C. 2(3x + 16)
Explanation:
If we replace x by 1 in the expression, we get:
4(1+ 1 + 7) - 2(1) + 8 - 4 = 4(9) - 2 + 8 - 4 = 38
If we replace x by 2 in the expression, we get:
4(2+ 2 + 7) - 2(2) + 8 - 4 = 4(11) - 4 + 8 - 4 = 44
Then, if we replace x=1 and x=2 on expression A, we get:
6x+11 = 6(1) + 11 = 17
6x + 11 = 6(2) + 11 =23
if we replace x=1 and x=2 on expression B, we get:
3(x + 7) = 3(1 + 7) = 24
3(x + 7) = 3(2 + 7) = 27
if we replace x=1 and x=2 on expression C, we get:
2(3x + 16) = 2(3(1) + 16) = 38
2(3x + 16) = 2(3(2) + 16) = 44
if we replace x=1 and x=2 on expression D, we get:
3x + 16 = 3(1) + 16 = 19
3x + 16 = 3(2) + 16 = 22
Finally, the answer is C, because we get the same answers as in the initial equation